Complex questions about combined hormonal contraception: A review - Vera N. Prilepskaya; Lana L. Bostandzhian (IP Berlin A.V., 2023)
Combined oral contraceptives (COCs) containing synthetic analogs of sex steroids are considered the most effective and popular method of contraception worldwide. The low rate of hormonal contraceptive use is often because of the fear of side effects due to existing myths. Complex questions that most often arise among doctors and patients when choosing COCs include the risk of thrombosis and cancer, the effect on fertility after the use of COCs, the use of COCs in patients with COVID-19, etc. COCs are highly effective, well-studied, and pose minimal risks that are well understood, described in the labels, and can be avoided with proper use.